Research in organizational change and development. Vol. 27 - Shani, Abraham B. Rami; Noumair, Debra A. (Emerald Publishing Limited, 2019)
Volume 27 of Research in Organizational Change and Development introduces thought-provoking insights on inclusivity within organizations. These include: the philosophical foundation of organization development and change; positive organizational scholarship as a scientific base for sustainable change; the practice of humility and humble behaviors; a socio-economic approach to organization development enhancing the compatibility between the human system, stakeholders, and stockholders; the importance of collaborative effort across hierarchies and vertical boundaries, despite tensions that undermine middle managers' role as change agent; the use of top-down and bottom-up processes to link attitudes and enhance levels of engagement; how leaders in social enterprise development continuously respond to common paradoxes of engagement; and, finally, enhancing a culture of inclusive, agile and thriving teams in environments of continuous change. The diverse collaborative contributions by leading scholars and scholar-practitioners from across the globe provide an enriching body of knowledge on contemporary challenges in organizational change and development.
Prelims -- Toward a social science philosophy of organization development and change -- Positive organizational scholarship and agents of change -- Humility as an enabler of organizational growth and change -- A socio-economic approach to organizational development: case study of a socio-economic intervention in the Belgium subsidiary of a large company traded on Wall Street -- Key tensions in purposive action by middle managers leading change -- Facilitating change through groups: formation of collective attitudes toward change -- Leading in social entrepreneurship: developing organizational resources in confrontation with paradoxes -- Exploring agile thriving teams in continuous change environments -- About the contributors.
Print version record
Keywords: Organizational change; Business & Economics -- Organizational Development; Organizational theory & behaviour